Investigation of the PABPC1-BTG2 interaction and its effects on mRNA deadenylation by CNOT7(CAF1) - Ameerul Moominin, Aalam Mohammed (2022)
Polyadenylation is the process of the addition of a poly(A) tail to the 3ʹ end of mRNA. The binding of human poly(A) binding protein to the poly(A) tail can either initiate or repress translation or regulate mRNA degradation. Cytoplasmic mRNA degradation in eukaryotes involves shortening of mRNA poly(A) tail by poly(A)-selective ribonuclease (deadenylase) enzymes. A recent study reported that PABPC1 could stimulate deadenylation by CNOT7/CAF1, a catalytic subunit of the CCR4-NOT complex, in the presence of BTG2. BTG2 is antiproliferative, regulating cell cycle progression in various cell types. BTG2 bridges PABPC1 and CNOT7/CAF1 and regulates deadenylation. This study aims to understand how PABPC1 and BTG2 interact, starting by identifying the amino acid residues of PABPC1 and BTG2 that contribute to the interaction.